The role of adatoms in chloride-activated colloidal silver nanoparticles for surface-enhanced Raman scattering enhancement - Leopold, Nicolae; Stefancu, Andrei; Herman, Krisztian; Tódor, István Sz.; Iancu, Stefania D.; Moisoiu, Vlad; Leopold, Loredana F. (Beilstein Journal of Nanotechnology, 2018)
Chloride-capped silver nanoparticles (Cl-AgNPs) allow for high-intensity surface-enhanced Raman scattering (SERS) spectra of cationic molecules to be obtained (even at nanomolar concentration) and may also play a key role in understanding some fundamental principles behind SERS. In this study, we describe a fast (<10 min) and simple protocol for obtaining highly SERS-active colloidal silver nanoparticles (AgNPs) with a mean diameter of 36 nm by photoconversion from AgCl precursor microparticles in the absence of any organic reducing or capping agent. The resulting AgNPs are already SERS-activated by the Cl− ions chemisorbed onto the metal surface where the chloride concentration in the colloidal solution is 10−2 M. Consequently, the enhanced SERS spectra of cationic dyes (e.g., crystal violet or 9-aminoacridine) demonstrate the advantages of Cl-AgNPs compared to the as-synthesized AgNPs obtained by standard Ag+ reduction with hydroxylamine (hya-AgNPS) or citrate (cit-AgNPs). The results of SERS experiments on anionic and cationic test molecules comparing Cl-AgNPs, hya-AgNPs and cit-AgNPs colloids activated with different amounts of Cl− and/or cations such as Ag+, Mg2+ or Ca2+ can be explained within the understanding of the adatom model – the chemisorption of cationic analytes onto the metal surface is mediated by the Cl− ions, whereas ions like Ag+, Mg2+ or Ca2+ mediate the electronic coupling of anionic species to the silver metal surface. Moreover, the SERS effect is switched on only after the electronic coupling of the adsorbate to the silver surface at SERS-active sites. The experiments presented in this study highlight the SERS-activating role played by ions such as Cl−, Ag+, Mg2+ or Ca2+, which is a process that seems to prevail over the Raman enhancement due to nanoparticle aggregation.
Keywords: chloride activation; electronic coupling; photoreduction; silver nanoparticles; SERS-active sites; SERS switch-on effect